Pengaruh Digital Nudging terhadap Purchase Intention pada Pengguna Aplikasi E-Grocery - Ramdhan Tri Fauzan; Terrylina Arvinta Monoarfa; Fildzah Shabrina (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the effects of perceived personalization, Default Policy, and nudges framing on Purchase intention among users of the Alfagift e-grocery application, with perceived usefulness as a mediating variable. The research is motivated by the rapid growth of e-grocery in Indonesia, which is accompanied by high food loss and opportunistic, promotion-sensitive consumer behavior, thereby requiring digital nudging interventions at the interface level to encourage more responsible consumption patterns. A quantitative survey approach is employed using purposive sampling targeting Millennial and Generation Z users of Alfagift in DKI Jakarta who have made at least one purchase in the last three months, with constructs measured using a Likert scale and data analyzed through Structural Equation Modeling (SEM) based on Partial Least Squares (PLS-SEM) using SmartPLS. The findings are expected to show that perceived personalization, Default Policy, and nudges framing have positive effects on Purchase intention, both directly and indirectly through perceived usefulness, thereby strengthening the integration of Nudge Theory and the Technology Acceptance Model (TAM) in the e-grocery context and offering practical implications for designing digital nudging strategies to reduce food loss.